Recent advance on Co‐based materials for polysulfide catalysis toward promoted lithium‐sulfur batteries. Issue 2 (26th July 2021) - Qiu, Saisai; Liang, Xinqi; Li, Yu; Xia, Xinhui; Chen, Minghua
Abstract: Lithium‐sulfur batteries (Li‐S batteries) have been regarded as one of the most promising technologies to change the status quo of lithium‐ion battery and realize large‐scale energy storage applications. Nevertheless, the process of launching Li‐S batteries from lab to market is seriously hindered by their inherent shortages (for example, shuttled lithium polysulfides (LiPSs), and sluggish redox kinetics), which greatly restrict sulfur utilization and the battery cycle life. In this regard, Co‐based materials are effective to suppress the shuttle effect through anchoring soluble LiPSs and enhancing reaction kinetics. It is of great significance for the development of advanced catalytic materials to clarify the research progress of Co‐based materials in design strategy, modification mechanism and electrochemical properties. Considering this, we conduct a comprehensive review of recent progress with Co‐based materials utilized in Li‐S batteries. Specifically, the state‐of‐the‐art principles, challenges, and build strategies of Li‐S batteries are systematically summarized. Meanwhile, the chemical and catalytic interactions between the Co‐based materials and LiPSs, as well as energy storage performance of Co‐based materials are thoroughly discussed. Finally, we prospect the future opportunities and challenges for the practical application for advanced Li‐S batteries. Abstract : Co‐based materials are effective to suppress the shuttle effect through anchoring soluble LiPSs and enhancing reaction kinetics. Herein, an overview of recent advancement of Co‐based materials utilized in Li‐S batteries is presented, including the state‐of‐the‐art principles, challenges, build strategies, as well as energy storage performance of Co‐based materials used in Li‐S batteries are systematically summarized.